PENGARUH KUALITAS, HARGA DAN CITRA PRODUK TERHADAP KEPUASAN PELANGGAN PADA PRODUK KOSMETIK WARDAH (Studi pada Mahasiswi Fakultas Ekonomi Islam Batik Surakarta) - Lela Novita Anggraini; Eny Kustiyah; Sudarwati Sudarwati (EKOBIS, 2019)
The purpose of study was to determine the effect of quality, price, and product image on customer satisfaction on Wardah cosmetic products. The research subjects were 100 students from UNIBA Surakarta Faculty of Economics. Data collection is based on documentation and field data in the form of answers to questionnaires that have been distributed. The analytical tool used is test data instruments, classic assumption tests and multiple linear regression. The results showed that simultaneously the quality, price and brand image had a significant effect on the customer satisfaction of Wardah cosmetic beauty products at UNIBA Surakarta Economics Faculty students. Shown by the calculation obtained F count > Ftable and the first hypothesis proved to be true. Partially product quality has a significant effect on customer satisfaction of UNIBA Surakarta Faculty of Economics students, this is indicated by the value of t count > t table and the second hypothesis is proven to be true. Partially the price of the product has a significant effect on customer satisfaction of the UNIBA Surakarta Economics Faculty student, this is indicated by the value of t count > t table and the third hypothesis is proven to be true. Partially the product image has a significant effect on customer satisfaction of UNIBA Surakarta Faculty of Economics students, this is indicated by the value of t count > t table and the fourth hypothesis is proven to be true. Keywords: Quality, Price, Image, Customer Satisfaction